Analysis of Production Risks and Factors Affecting the Risk of Ornamental Fish Farming Business in Plosoklaten District, Kediri Regency - Supriyadi Supriyadi; Mariyana Sari; Kartika Intan Abdillah; Chusnia Asshovani (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
Cultivators who are in business will confront various external and internal problems that may result in losses and uncertainty. The incident was caused by the risks that ornamental fish producers faced. If the production risk is high, it should be avoided otherwise, if the production risk is low, it should be handled more thoroughly. The purpose of this research is to determine the amount of risk associated with ornamental fish production using risk maps and to discover factors that influence ornamental fish production risk. The census was used as a sampling method, with a sample of 36 respondents. The data used is a combination of primary and secondary sources. Data analysis methods applied include descriptive and analytical methods such as variance analysis, standard deviation, coefficient variation, risk level based on risk map, and risk function based on the Just and Pope model form. Based on coefficient variation values and risk maps of 1.05, the risk level of ornamental fish production indicates that farmers' production risks are classified as high risk. Feed factors have a significant impact on the risk of ornamental fish production, whereas labor, pond space, medicines, and fish seeds have no significant effect on the risk of ornamental fish production.